Detection of Antibody against Helicobacter pylori in the Saliva of Patients with Dyspepsia - Robert L Clancy; Allan W Cripps; Diana C Taylor; Lois A McShane; Victor J Webster (Canadian Journal of Gastroenterology)
There is a need to develop noninvasive assays to detect Helicobacter pylori infection in the gastric mucosa, Current dogma predicts that the presence of antibody within saliva should accurately reflect contemporary colonization of the gut mucosa. This study examined the clinical value of a saliva enzyme-linked immunoadsorbent assay (ELISA) for anti-H pylori antibody, compared with the serum ELISA assay, and found the sensitivity of the saliva assay was 89%, specificity 94%, accuracy 93%, positive predictive value 89% and negative predictive value 94%. Assessment following eradication therapy demonstrated that salivary antibody was a more sensitive indicator of colonization than was serum antibody. The immunoglobulin G antibody in saliva correlated best with colonization, and regression analysis was most consistent with a local production of antibody. These results indicate that detection of antibody in saliva contributes to diagnosis and management of H pylori infection.